Habitat use governs distribution patterns of saprophagous (litter-transforming) macroarthropods - a case study of British woodlice (Isopoda: Oniscidea) - Bethan V. PURSE; Steve J. GREGORY; Paul HARDING; Helen E. ROY (European Journal of Entomology, 2012)
Despite the importance of saprophagous macroarthropods as key facilitators of plant litter decomposition within ecosystems and their likely sensitivity to global climate change and land-use change, a lack of ecological data has precluded attempts to explain their distribution patterns in terms of traits. Using an extensive set of large-scale and long-term biological records, the distribution patterns of 33 woodlice (Crustacea: Oniscidea) species in Britain were characterised by their range size (area of occupancy) and aggregation (degree to which occupied squares are clustered across the range). Body size and seven ecological traits were examined as correlates of range size and fill, while controlling for phylogeny and recording intensity, and comparing fine and broad-scale measures of habitat heterogeneity. Species that used a greater diversity of habitats had larger range sizes. Broad categorisation of habitats (by dominant vegetation) alongside other traits was less accurate in predicting range size than fine-scale habitat (microsites where individuals were discovered) data. The latter explained 25% more variance than broad-scale habitat data, highlighting the value of coupling biological recording of species with data on micro-habitat. Habitat use is an important trait in explaining distribution patterns and we conclude that ensuring land cover heterogeneity will favour conservation of saprophagous macro-arthropod diversity.